2015
DOI: 10.1371/journal.pone.0134893
|View full text |Cite
|
Sign up to set email alerts
|

Rescue of Fructose-Induced Metabolic Syndrome by Antibiotics or Faecal Transplantation in a Rat Model of Obesity

Abstract: A fructose-rich diet can induce metabolic syndrome, a combination of health disorders that increases the risk of diabetes and cardiovascular diseases. Diet is also known to alter the microbial composition of the gut, although it is not clear whether such alteration contributes to the development of metabolic syndrome. The aim of this work was to assess the possible link between the gut microbiota and the development of diet-induced metabolic syndrome in a rat model of obesity. Rats were fed either a standard o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

10
130
2
1

Year Published

2016
2016
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 151 publications
(143 citation statements)
references
References 47 publications
10
130
2
1
Order By: Relevance
“…Rodent data indicate that Coprococcus increases in fructose-fed animals, which develop metabolic syndrome. Coprococcus decreases in animals after either antibiotic treatment or faecal transfer, which improved their metabolic phenotype 44. In contrast, another MGS cluster was composed of species strongly reduced with increasing trunk-fat.…”
Section: Discussionmentioning
confidence: 98%
“…Rodent data indicate that Coprococcus increases in fructose-fed animals, which develop metabolic syndrome. Coprococcus decreases in animals after either antibiotic treatment or faecal transfer, which improved their metabolic phenotype 44. In contrast, another MGS cluster was composed of species strongly reduced with increasing trunk-fat.…”
Section: Discussionmentioning
confidence: 98%
“…The experimental animals were fed an HFD or highfructose diet to establish the metabolic syndrome or DM model (20,21). Therefore, this study examined the histopathology of the livers and kidneys of C57BL/6J mice 1145…”
Section: Abstract Background/aim: Metabolic Syndrome-induced Lifestymentioning
confidence: 99%
“…Furthermore, only a few studies such as that of Moroki et al (19) have reported experiments showing the effects of Zn complexes on lipid metabolism. Thus, the effects of Zn compounds on lipid metabolism have not been sufficiently examined yet.The experimental animals were fed an HFD or highfructose diet to establish the metabolic syndrome or DM model (20,21). Therefore, this study examined the histopathology of the livers and kidneys of C57BL/6J mice 1145…”
mentioning
confidence: 99%
“…This amounts to an ethanol elimination rate of 528 g per day, without including gastric, colonic, and hepatic FPM. This key role of gut microbiota in FPM of ethanol is supported by studies showing that oral antibiotics protect against both NAFLD/NAFPD [130][131][132][133][134] and alcoholic liver disease [135]. Furthermore, germ-free animals are also protected against dietinduced obesity-related disorders [136][137][138] as well as ethanol-induced liver injury [139].…”
Section: Discussionmentioning
confidence: 98%